1993
DOI: 10.1254/jjp.62.387
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of ATP-Sensitive K+ Channels in the Inhibition of Rat Central Adrenergic Neurotransmission under Hypoxia

Abstract: ABSTRACT-The role of cyclic GMP (cGMP) in nonadrenergic, noncholinergic (NANC) relaxation of the longitudinal muscle of rat proximal and distal colon was examined. Electrical field stimulation (EFS) of preparations of longitudinal muscle from the proximal region significantly increased the cGMP content. Nitro-L-arginine inhibited this increase, and L-arginine reversed the inhibitory effect of nitro-L-arginine. Exogenously added nitric oxide (NO) and atrial natriuretic peptide (ANP) also increased the cGMP cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
4
8
0
Order By: Relevance
“…However, the same concentration of the inhibitor did not affect the DMPP-and EFS-induced relaxations (Table 1) not only the stimulatory effect of DMPP on the cyclic GMP content and decreased it below the resting level ( Figure 3). As we have already shown, EFS also increased the cyclic GMP content of the preparations (Suthamnatpong et al, 1993b;Figure 4).…”
Section: Dmpp-induced Relaxationsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the same concentration of the inhibitor did not affect the DMPP-and EFS-induced relaxations (Table 1) not only the stimulatory effect of DMPP on the cyclic GMP content and decreased it below the resting level ( Figure 3). As we have already shown, EFS also increased the cyclic GMP content of the preparations (Suthamnatpong et al, 1993b;Figure 4).…”
Section: Dmpp-induced Relaxationsupporting
confidence: 78%
“…EFS of the preparations significantly increased the guanosine 3':5'-cyclic monophosphate (cyclic GMP) content and L-NOARG inhibited while L-arginine reversed this inhibition. Exogenous nitric oxide increased the cyclic GMP content of the preparations (Suthamnatpong et al, 1993b). We also showed a relaxant effect of cyclic GMP in 'skinned smooth muscle' preparations obtained from the longitudinal muscle layer of rat proximal colon (Maehara et al, 1994).…”
Section: Introductionsupporting
confidence: 55%
“…Our previous studies suggested that NANC relaxation in longitudinal muscle of the rat distal colon was not associated with the nitric oxide-cyclic GMP generating system (Suthamnatpong et al, 1993a), although EFS or exogenous nitric oxide significantly increased cyclic GMP content of the colonic longitudinal muscle with myenteric plexus preparations (Suthamnatpong et al, 1993b;Maehara et al, 1994). Our present study strongly suggests that NANC-induced relaxation in the longitudinal muscle of the rat distal colon is mediated by VIP and PACAP which activate charybdotoxinand apamin-sensitive K+ channels, respectively.…”
Section: Discussionsupporting
confidence: 59%
“…NO is known to increase the intracellular cyclic GMP content through an activation of soluble guanylate cyclase in vascular smooth muscles (7). It was also shown that NO or EFS which induces NO-mediated relaxation, increased the cyclic GMP content in the smooth muscle cells in the rat ileum (8) and proximal colon (9). These results suggest that NO induces the relaxation of smooth muscle by increasing the cyclic GMP content.…”
Section: +mentioning
confidence: 88%